The Praonan Tradition in Pasuruans City Plays An Instrumental Role in Maintaining Social Harmony and Tolerance - Khamid, Abdul; Safiq, Abdulloh; Lailyah, Faridatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The integration of Islamic values through local wisdom is a significant factor in maintaining social harmony and tolerance. This research aims to preserve the original culture of Indonesian society and examine the influence of integrating Islamic values and local wisdom through the Praonan tradition in Pasuruan City. This research is qualitative in nature, employing in-depth interviews with community leaders in conjunction with continuous observation and analysis to ensure the collection of valid data. The findings of this research indicate that the Praonan tradition is in alignment with Islamic values, which serve to facilitate the maintenance of social tolerance. This research contributes to the advancement of literacy and provides empirical evidence regarding the impact of applying local wisdom on the formation of social behavior. It is hoped that this research will facilitate a greater understanding of local culture and provide insight into the practice of social tolerance in Indonesia.